(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Transscleral cyclophotocoagulation (TSCPC) is a cyclodestructive procedure used to control elevated intra ocular pressure(IOP) in refractory glaucoma. We studied the efficacy and safety of TSCPC in refractory glaucoma at our hospital. Method: Data was collected retrospectively from patients who underwent TSCPC over a two year period. Primary outcome measure was success in terms of IOP reduction and the secondary outcome measures were relief of symptoms and incidence of complications. Results: 27 of 42 patients who underwent TSCPC were included for analysis which included 16 men and 11 women with mean age 61.8±13years and visual acuity ranging from 6/24 to no perception of light. Mean IOP decreased from 46.0±8.6 mmHg(range: 26-58 mmHg) pre-procedure to 16.7±13.4 mmHg(p<0.001) at last follow-up. Complete success was achieved in 22.2%, qualified success in 18.5%, 29.6% eyes had hypotony and 29.6% failed. Mean glaucoma medications decreased from 3.2±1.3 to 0.9±1.2(p<0.001). Patients were asymptomatic; complications were phthisis and vitreous hemorrhage which resolved (one case each). Conclusion: TSCPC is a safe and effective method of controlling IOP in refractory glaucoma. It may not be restricted to eyes with poor vision potential and a pain-free patient is often the end result.